ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA DI KALANGAN MAHASISWA POLITEKNIK KOTABARU - Renny Yunita; Dayat Ikhsan Hajati (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2019)
The aims of the study were to analyze the factors that influence the intention of entrepreneurship among students, such as educational support, relational support, personal attitudes and behavioral control factors. This study took a sample of 60 students by using purposive sampling technique. The data analysis technique used in this study was multiple linear regression analysis. The results showed that 1) there was a partial significant influence of educational support on students' entrepreneurship intention but had a negative causality pattern, the effect was -36.3%, 2) relational support had a positive causality pattern, but did not have a significant partial effect on students’ entrepreneurship intention, the effect was 12.7%, 3) there was a partial and positive significant effect, personal attitudes on students’ entrepreneurship intention and has the most dominant effect than other independent variables with a significant effect was 39.8%, 4) there was a significant effect and partially positive, behavioral control on students’ entrepreneurship intention with a signifikcant effect was 30.0%.